Effect of FRP on the Energy Absorbed by Steel Shear Walls with Openings - Mojtaba Ghasemzadeh (Iranian Society of Structrual Engineering (ISSE), 2015)
It’s for more than three decades that Steel Shear Walls are being used as lateral load resisting system. Definitely,the actual behavior of steel shear walls can be assessed using experimental results. However, solve many of phenomenon like this one should be done using mathematical and theoretical methods due to their special characteristics such as high expenses, lack of laboratory facilities and time limitations. In this study, the behavior of steel plate shear walls with openings in a one-story frame were evaluated and compared in various conditions. For this purpose, different values ​​for the opening in shear wall was considered and exposed to lateral displacement in ABAQUS as a comprehensive finite element software. Then, the impact of FRP arrangement on shear wall was evaluated to represent the structural behavior under various conditions. Result shows that, use of FRP sheets as parallel layers on both sides of shear wall has the best response on energy absorption, so that performance of the model was better than shear wall fully covered with FRP.